2013
DOI: 10.1049/el.2013.0319
|View full text |Cite
|
Sign up to set email alerts
|

Potential of MISFET with HfN gate dielectric formed by ECR plasma sputtering

Abstract: A report is presented on a Al/HfN/p-Si(100) n-MISFET with excellent electrical properties that inserts a 4 nm-thick HfN gate dielectric with equivalent oxide thickness of 0.7 nm formed by electron-cyclotronresonance plasma sputtering. The threshold voltage (V th ) of the device was 0.05 V. The on/off ratio and subthreshold swing at W/L = 90 µm/ 5 µm were ∼10 3 and 200 mV/dec., respectively. In particular, the n-MISFET exhibits I DS,sat = 20.2 µA/μm and g m = 20.5 mS/mm. This is the first report of n-MISFET cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…We have reported various Hf-based high-k gate insulators and also in-situ formation of HfN x (x < 1:0) gate electrode on the Hf-based high-k gate insulator [10,11,12,13,14]. It was found that the in-situ formation of HfN x (x < 1:0) gate electrode improved the electrical characteristics of Hf-based high-k gate insulator [13].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…We have reported various Hf-based high-k gate insulators and also in-situ formation of HfN x (x < 1:0) gate electrode on the Hf-based high-k gate insulator [10,11,12,13,14]. It was found that the in-situ formation of HfN x (x < 1:0) gate electrode improved the electrical characteristics of Hf-based high-k gate insulator [13].…”
Section: Introductionmentioning
confidence: 97%
“…It was found that the in-situ formation of HfN x (x < 1:0) gate electrode improved the electrical characteristics of Hf-based high-k gate insulator [13]. HfN x is well known that it also shows dielectric properties when the nitrogen concentration is higher than hafnium concentration (x > 1:0) [14]. In this paper, we investigated the in-situ formation of Hf-based MONOS structure, such as HfN x (x < 1:0)/HfO 2 /HfN x (x > 1:0)/HfO 2 /Si(100), utilizing electron-cyclotronresonance (ECR) plasma sputtering in a chamber by changing the process gasses for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the interfacial layer (IL) with relatively low-dielectric constant between high-κ/Si interfaces is formed easily when the oxide-based high-κ gate insulator is used [5]. Therefore, nitride dielectrics are the candidate materials as a gate dielectric to overcome the problems of oxide-based high-κ materials to suppress IL formation [6,7]. We have reported that 0.5 nm EOTs were obtained by using hafnium nitride (HfN) gate insulator (I) formed by electron-cyclotron-resonance (ECR) plasma sputtering with ex-situ Al gate electrode (G) [8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to realize the adequate device scaling, various new materials have been introduced in the MOSFETs [1][2][3][4][5][6] especially for the gate stack structures [7][8][9][10][11]. With the device scaling, ultrathin gate insulator is necessary to be introduced.…”
Section: Introductionmentioning
confidence: 99%